Radicalism VS Extremism: The Dilemma of Islam And Politics In Indonesia - Muhammad Adnan; Anita Amaliyah (JURNAL ILMU SOSIAL, 2021)
Despite its adherence to the principles of democracy, Indonesia is currently trapped in conditions and situations over the emergence of a new government system based on Islam. The notion of extremism dominates society, both the general public and the political elite, and has even infiltrated the youth via the education system. Community mobilization movements in the name of religion in the political sphere indicate that extremism has spread and is gaining strength. The main focus of this research is to make a clearer distinction between radicalism and extremism from both a political and religious perspective. To answer this problem, this paper clarifies the meaning of the terms “extreme” and “radical” in the context of religious politics from the point of view of democracy and distinguishes the signs for the two dimensions of extremism and radicalism. Not only that, in this study there are also explanations related to religious phenomena which basically have an indirect relationship with politics and extremism. This study approach uses a qualitative method taken from the study of Borum and Schmid. It argues that the difference between extremism and radicalism rests on the existence of an ideology. Radicalism is a form of process in which there is agreement or disagreement on violence in tactical and temporal considerations, while the concept of extremism is considered a motive.